Implementasi Program Jaminan Kesehatan Pekanbaru Bertuah di Kota Pekanbaru - Firda Ayuni Safyentri; Mimin Sundari Nasution (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research is motivated by the continued inability of the people of Pekanbaru City to finance health services for their families and themselves, where health is fundamental in meeting life's needs. Therefore, the Pekanbaru City Health Service created an innovative health insurance program to achieve Universal Health Coverage (UHC) which was named Pekanbaru Bertuah Health Insurance to make it easier for the people of Pekanbaru City to access health to improve the welfare of the people of Pekanbaru City. Pekanbaru Bertuah Guarantee is a health insurance service that is free of charge only by using an ID card for those domiciled in Pekanbaru City. The aim of this research is to find out how the Pekanbaru Bertuah Health Insurance Program is implemented. The method used in this research is a qualitative research method. With data collection techniques, namely interviews, observation and documentation. The results of the research show that the im plementation of the Pekanbaru Bertuah Health Insurance Program carried out by the Pekanbaru City Health Service is not optimal, this can be proven by the existence of several obstacles found in implementing the Pekanbaru Bertuah Health Insurance Program, namely that there are still many people who do not know about the Pekanbaru Bertuah Health Insurance Program. Many people have not been able to register for the Pekanbaru Bertuah Health Insurance Program and the collaboration between the Pekanbaru City Health Service and hospitals is not yet comprehensive.